No correlation between mtDNA amount and methylation levels at the CpG island of POLG exon 2 in wild-type and mutant human differentiated cells. Issue 5 (9th January 2017) - Steffann, Julie; Pouliet, Aurore; Adjal, Houda; Bole, Christine; Fourrage, Cécile; Martinovic, Jelena; Rolland-Galmiche, Louise; Rotig, Agnes; Tores, Frédéric; Munnich, Arnold; Bonnefont, Jean-Paul
Abstract : Background: While mitochondrial DNA (mtDNA) copy number is strictly regulated during differentiation and according to cell type, very little is known regarding the mechanism which accurately controls mtDNA copy number in human. Exon 2 of the human POLG gene, encoding the catalytic subunit of the mitochondrial-specific DNA polymerase gamma, contains a CpG island, highly conserved in mice and human. Changes of DNA methylation at the POLG locus have been shown to modulate mtDNA copy number during cell differentiation in both mouse and human. Methods: We have investigated the epigenetic modification of the POLG gene, by assessing the methylation level of its exon 2 using deep-Next Generation Sequencing analysis of bisulfite-treated DNA. Analysis were performed on various tissues at either postnatal or prenatal stages, on samples from carriers of mtDNA mutations, patients carrying two loss-of-function POLG mutations and controls. Results: Very high methylation levels at POLG exon 2 were found (94±3%) and no variation was observed according to either developmental stage or tissue of origin, except for sperm samples for which lower methylation levels were found (80%). This high level of methylation was neither correlated with the presence of mtDNA mutations (94±1% of methylated alleles), nor with biallelic POLG mutations (93%±2%), even in tissues where a mtDNA depletion had been observed. Conclusions: This study suggests that, at variance with mouse and un/de-differentiated human cells, differentiated human cells control mtDNA levels irrespective of POLG methylation. The factors which actually control the mtDNA levels in such cell types remain to be identified.